PENGARUH CITRA MEREK, KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PIZZA HUT - Arifiana, Latifa; Aqmala, Diana; Cahya, Handy Nur; Damar, Haunan (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
The reason for this study was to determine the impact of brand image, product quality, and promotion on purchasing decisions of Pizza Hut consumers. The population is Pizza Hut customers, with a sample of 150 respondents taken using non-probability sampling techniques with purposive sampling method. PLS was used as an analytical tool in this study. This study shows that brand image has a positive, but insignificant, impact on purchasing decisions of Pizza Hut consumers. On the other hand, product quality has a positive and significant impact on purchasing decisions of Pizza Hut consumers. In addition, promotion also has a positive and significant impact on purchasing decisions of Pizza Hut consumers.